Identifying the Effective Factors and the Importance of the Harirud Watershed in Afghanistan and its Impact on Iran - Fayaz Gul Mazloum Yar; Mullajan Rahmani; Ebadullah Amir (Randwick International of Social Science Journal, 2023)
One of the problems in the analysis of Hydro politics relations in the international river system is that the same factors can create a diverse range of conflict or cooperation, and even the same variable may play a different role in relation to other variables in each coastal country. Therefore, it is necessary to know the variables and the role that each variable plays in formulating a model for analyzing opportunities and risks for countries that share a watershed with other countries. One of the fundamental measures in the analysis of Hydro politics relations in the transboundary river system is to know the variables. Which play a role in the importance of transboundary waters for countries. Harirud water enters Iran from Afghanistan, and the location of its catchment area in the arid and semi-arid region of the world has made them dependent on Harirud water to meet their water needs. Afghanistan's development programs have caused a decrease in Harirud water entering Iran in such a way that it can create a challenge to Iran's security. Therefore, the question of the research is, what are the variables and indicators influencing the strategic importance of Harirud for Afghanistan, and what is its effect on Iran? For this purpose, 68 identification indicators and data were analyzed using the Delphi method and structural analysis method with Micmac software. In this research, 35 experts were selected, of which 25 participated in completing the Delphi questionnaires and 10 participated in completing the questionnaire of the mutual effects analysis matrix, and the answers of 8 of them were used to complete the matrix. is placed Based on the findings of the research, indicators of the importance of Harirud for national security, security of water resources, and implementation of economic development programs for Afghanistan are considered strategic indicators.